Day care cataract surgery in Central and Southern Italy: a multicentric survey - Cillino Giovanni; Pillitteri Francesco; Di Pace Francesco; Casuccio Alessandra; Cillino Salvatore; Lodato Gaetano (BMC, 2007)
Abstract Background Cataract day surgery has rapidly gained worldwide acceptance, because the new surgical techniques and costs are generally lower than those involved in ordinary hospitalization. Cataract surgery serves as a proxy indicator of the trend towards day surgery hospitalization in Italy and, therefore, of regional variability in health-care delivery and cost. The aim of this study was to update the diffusion of cataract day surgery through various surgical ophthalmological centers in central and southern Italy during 2005. Methods A two-stage stratified cluster sampling method was used to draw a sample of Cataract Surgery Unit from Ophthalmic Units of central and southern Italy. A questionnaire was sent to 25 cataract surgery centers in nine health districts that represented the range of establishments (public, private, accredited or otherwise) in which cataract surgery is performed. Data were collected on numbers of procedures performed in 2005, hospital admission type, time from the onset of cataract day surgery, surgical procedure, and presence of other surgical centers. Results The response rate was 42% (10 surveys), resulting in at least one completed questionnaire for each of these 9 districts. There is a positive trend towards day surgery hospitalization in all surgical centers. The percentage of patients treated as outpatients during 2005 varied from 50-60% (Avellino, Naples, Campobasso), to 80-90% (Rome, Bari), up to 90-100% (Catania, Palermo, Siracusa and Trapani), with an increasing trend in all the centers studied. Few differences were found in surgical procedures, and these were statistically insignificant. Conclusion Our results confirm a positive trend towards day surgery in place of hospital inpatient admission for cataract surgery. This trend is expected to close the existing regional gap in Italy. Increased efficiency is an overriding need for the National Health Service in order to improve the rationalization of resources.